Evaluation of the pedagogical leadership of the principal and its relationship with the teaching performance in the educational institution N ° 2069 Santa Rosa. Ugel 04. District of Puente Piedra. Lima Region 2017 - Obregón Castillejo, Liz Daicy (2020)
The scientific research we have conducted is basic, non-experimental causal correlation, the study factors are two: Evaluation of the Pedagogical Leadership of the Director and his Relation with the Teaching Performance in the Educational Institution N ° 2069 Santa Rosa. UGEL 04. Puente Piedra District. Lima Region 2017. The population is made up of 2 Directors and 56 Teachers. The research design is transactional, correlational, causal. bivariate, transversal. Two questionnaires were drawn up for the data collection: one for the variable Pedagogical Leadership of the director and the other for a variable evaluation of the teaching performance, which was applied to the 2 Directors and 56 Teachers of the sample. The instruments comply with the qualities of validity and reliability. The study proposes the following research hypothesis: Evaluation and Pedagogical Leadership of the Director and his Relation with the Teaching Performance in the Educational Institution N ° 2069 Santa Rosa. UGEL 04. Puente Piedra District. Lima Region 2017. The results obtained allow us to reject the null hypothesis and accept the hypotheses investigated because it has been found in a non-parametric test therefore Kruskal-Wallis test was applied to observe the significant relationship between pedagogical leadership and teaching performance with a level of significance of 95% obtaining a value of 0.00, in addition the lineal regression test was applied and it was obtained that the pedagogical leadership is related in a 42.4% with the teaching performance therefore the null hypothesis is rejected and the hypothesis is accepted alternate research.